Pengembangan Modul Pembelajaran Biologi Berbasis Sains Islam untuk Meningkatkan Imtaq Siswa Kelas XI SMA Negeri 7 Kota Bengkulu - Simbuldin; Irwandi; Nopriyeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aims to develop a valid and practical Islamic science-based biology learning module to enhance faith and piety (iman and taqwa) of grade XI students at SMA Negeri 7 Bengkulu City. The research method used Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Research subjects included 4 expert validators for validity testing and 35 students for practicality testing. Data analysis techniques used descriptive percentage analysis. The results showed that the Islamic science-based biology learning module was declared very valid with an average percentage of 84% and very practical with a percentage of 88%. Student responses to the improvement of faith and piety reached 89% in the very good category. The conclusion of this research is that the Islamic science-based biology learning module is feasible and practical to use in reproductive system learning to enhance students' faith and piety. Keywords: Biology, Faith, Islamic Science, Learning Module, Piety